Comparativo de Densidades de Siembra del Cultivo de Yute (Urena lobata) en la zona del Alta Mayo - Región San Martin. - Villegas Córdova, Rafael (2001)
The present work was carried out in the town of Atumplaya, District and Country of Moyobamba (Area of the High May), Departament of San Martín; Whose location geographical location corresponds at the 6° 01'59 South Latitude, 76°5819' Longitude West and 874 m.s.n.m. The objective was to determine the density of the cultivation of Jute (Urena Lobata L), I lower you edafoclimáticas condition of the High May and to carry out the economic analysis of the treatments. The caracterististies of de soil and climate were: clay - oozy, with 7.5 of pH, with 3.0% of organic matter, with 11.4 ppm. Of P, with 101.6 ppm. of K, with 18.4 meq/gr of soil of CaMg, with annual half temperature of 23.16 °C and a precipitation I average yearly of 1,260 mm. The design experimental employee was that of blocks totally at random (DBCA), with 14 treatments and 4 repetitions. The seeding was made with seed coming frorn the town ofyurimaguas - Loreto. Likewise he/she was carried out the deshije arid the control of overgrowths. The crop was made to tbe 7 months. The process of the post - it harvests I last approximately 23 days, in which according to the parameters of quality the fiber was classified in 3 groups: fiber of first, fiber of second and fiber of third. The bigger fiber yield was obtained with the treatment Tl (3,448. IO Kg/Ha.) whose seeding distancing is of 20 x 15 cm., white the treatment T3 (20 x 25 cm.) was the most profitable ( 65% ), to ha ve a bigger yield of fiber of first quality ( 61 % ), because the accumulated entrance was of SI. 3,533.00/Ha, with a yield of 3,245.00 Kg./Ha. of fiber and a cost of production ofS/. 2,143.26/Ha. is. The distancing recommended as product ofthis investigation work is that of 20 x 25 cm., to be economically the most convenient.